Legal Protection for Franchisors and Franchisees in Cases of Breach of Franchise Agreement - Daniel Daniel; Ariawan Gunadi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study aims to analyze the effectiveness of Indonesia’s positive law in providing legal certainty and justice for the parties in resolving franchise disputes arising from breach of contract. The research uses a normative juridical method with a statutory and conceptual approach. The findings indicate that Indonesia’s legal framework on franchising has been comprehensively regulated under Government Regulation No. 42 of 2007, Minister of Trade Regulation No. 71 of 2019, and the Civil Code provisions. Normatively, these regulations have provided a foundation of legal certainty and protection for both franchisors and franchisees. However, the effectiveness of implementation remains limited due to the lack of administrative compliance among business actors, weak government supervision, and the inequality of bargaining power in standard contracts. Therefore, it is necessary to strengthen state supervision, enhance legal awareness among business actors, and enforce principles of justice and good faith in the execution of franchise agreements, so that the law not only ensures formal certainty but also achieves substantive justice for both parties.